The Impact of Capital, Land Area, and Labor on Shrimp Pond Income: An Islamic Economic Perspective - Putri, Kristina; Mu`awwanah (MALIA: Jurnal Ekonomi Islam, 2025)
Introduction: Shrimp farming is a significant economic sector in increasing income and driving regional economic growth. This study aims to analyze the effect of capital, land area, and labor on shrimp pond business income, and to identify factors that influence the development of shrimp pond businesses optimally. Methods: This study uses a quantitative method approach by applying multiple linear regression analysis and census methods to obtain a sample of 26 shrimp farming businesses. Data collection techniques through distributing questionnaires to shrimp farming entrepreneurs, data analysis is carried out with the support of statistical analysis software programs (SPSS25) to interpret the results and answer research questions. Results: From the results of this study, it was found that capital and land area significantly affect the income of shrimp farming businesses, while labor had a significant negative effect. These results highlight the role of capital, land area and labor in increasing business income. Conclusion and suggestion: By considering the findings of this study, shrimp farmers can take strategic steps to increase their business income, namely by optimizing conservation capital, land area utilization, and developing workforce skills. This study is expected to provide useful insights for the development of sustainable shrimp farming businesses.